Морфологія та життєздатність насіння інтродукованих видів роду Veronica L. у Донецькому ботанічному саду НАН України - Zybenko, O.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
Morphologic peculiarities and indications of seeds vitality of three introduced species of the genus Veronica L. and one hybryd according to the indices of energy of germination have been studied. It has been determined that the seed form index and sizes of seed specimens introduced from different populations are practically the same, except of the hybryd. Seed germination probably depends upon the origin of a specimen.